2018
DOI: 10.1093/toxsci/kfy183
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Transformation of Human Bronchial Epithelial Cells by Diesel Exhaust Particles: Gene Expression Profiling and Early Toxic Responses

Abstract: Occupational exposure to diesel exhaust may cause lung cancer in humans. Mechanisms include DNA-damage and inflammatory responses. Here, the potential of NIST SRM2975 diesel exhaust particles (DEP) to transform human bronchial epithelial cells (HBEC3) in vitro was investigated. Long-term exposure of HBEC3 to DEP led to increased colony growth in soft agar. Several DEP-transformed cell lines were established and based on the expression of epithelial-to-mesenchymal-transition (EMT) marker genes, one of them (T2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 60 publications
2
27
1
Order By: Relevance
“…The only exception was the increase in PGD 2 and the decrease in PGE 2 metabolites, which may suggest a slight induction of anti-inflammatory response [30] at low, non-cytotoxic concentration of PM0.5. Importantly, we found no significant modulation of levels of 8-iso-PGF 2alpha , 9-and 13-HODE, the markers of oxidative stress and lipid peroxidation [29,55], although oxidative stress is generally a well-accepted mechanism of nanoparticle-induced toxicity (e.g., [56]).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The only exception was the increase in PGD 2 and the decrease in PGE 2 metabolites, which may suggest a slight induction of anti-inflammatory response [30] at low, non-cytotoxic concentration of PM0.5. Importantly, we found no significant modulation of levels of 8-iso-PGF 2alpha , 9-and 13-HODE, the markers of oxidative stress and lipid peroxidation [29,55], although oxidative stress is generally a well-accepted mechanism of nanoparticle-induced toxicity (e.g., [56]).…”
Section: Discussioncontrasting
confidence: 53%
“…Additionally, changes in the levels of released arachidonic acid (AA) metabolites were examined by liquid chromatography-tandem mass spectrometry (LC-MS/MS) as they represent a functional readout of induction of oxidative stress and inflammation and/or anti-inflammatory response [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Líbalová et al (2014) reported strong upregulation of CYP1A1 and 1B1 gene expression upon exposure of human lung A549 cells to the extractable organic matters (EOMs) from the respirable fraction of airborne PM2.5 particles (< 2.5 µm) from three heavily polluted areas of the Czech Republic. Libalova et al (2016) demonstrated a considerable increase of CYP1A1 and 1B1 mRNA upon exposure of BEAS-2B cell line to diesel exhaust particles and Rynning et al (2018) demonstrated increases of the same CYPs mRNAs in HBEC3 (human bronchial epithelial cell line) upon exposure to diesel exhaust particles. Longhin et al (2016) observed increases in the mRNA levels of AKR1C1, 1C2 and 1C3 upon exposure of the BEAS-2B human lung cancer cell line to urban particulate matter and Libalova et al (2016) demonstrated in BEAS-2B cells a considerable increase of AKR1C2, 1C3 and 1C4 mRNA upon treatment with diesel exhaust particles.…”
Section: Some Examples Of Studies On Xenobiotica-metabolizing Enzyme mentioning
confidence: 95%
“…Eicosanoids, including prostaglandins, thromboxanes, and hydroxyeicosatetraenoic acids, are enzymatic oxidation products of arachidonic acid. Eicosanoids are biologically active lipid mediators with implication for inflammation and carcinogenesis 46,47 . Our data demonstrated that genes related to oxidative stress were not induced and no changes were detected in concentration levels of proinflammatory eicosanoids.…”
Section: Discussionmentioning
confidence: 99%